THE IMPORTANCE OF PLAYING IN THE LEARNING OF STUDENTS OF CHILD EDUCATION - Silva Ferreira, Gabrielly; Silva Francisconi, Poliana (Revista Gênero e Interdisciplinaridade, 2021)
The topic proposed by the article was of interest due to an extension project that I participated in in 2016. The extension project toyboard Toyteca Itinerante da Pedagogia, approved last year by the research and extension committee, brought a lot of interest in the area. The fact is that the project is focused only on bringing entertainment to public school students, in their spare time, it managed to show how children and schools have left games and games aside. And rescuing these games and games was very satisfying. And the article shows the importance of assimilating theoretical content with pedagogical practices. What school, teachers, students and parents need to have interactions with. And that since kindergarten, we must show the importance of working together, to be able to awaken the interest of students, and not let there be a gap in schools. Show that the teacher is the main mediator of the entire schooling process.